Environmental Conservation Units – a Pragmatist Analysis of the Organizational Management and Modes of Existence of an Ecological Station - Matarazzo, Gustavo; Serva, Maurício (Organizações & Sociedade, 2021)
Protected areas are the main instrument used for protecting and conserving nature (UN, 2018). In Brazil, these areas are called Unidades de Conservação (UCs), or Conservation Units in English, and despite their territorial coverage and the complexity of their problems, they have not been properly studied by the area of administration. As a result, in this article we aimed to broaden the understanding about the modes of existence, as well as about the management of a protected area in a particular territory. For this, we took a pragmatist epistemological approach, favoring action above all. The study material derives from ethnographic research using participant observation at a UC managed by the Chico Mendes Institute for Biodiversity (ICMBio). As results, we identified three distinct modes of existence of the organization, namely: environmental education; production of expertise; and protection and inspection of nature. The analysis of these modes of existence enabled a better understanding of how specific organizational configurations emerge that situationally position the actors in different ways, engendering collective action and its management. Finally, we forge arguments that highlight possible contributions of a pragmatist epistemology to the organizational analysis of UCs.